Utility of Methicillin-Resistant Staphylococcus aureus Nares Screening in Hospitalized Children with Acute Infectious Disease Syndromes - Ashley Sands; Nicole Mulvey; Denise Iacono; Jane Cerise; Stefan H. F. Hagmann (MDPI AG, 2021)
Studies in adults support the use of a negative methicillin-resistant Staphylococcus aureus (MRSA) nares screening (MNS) to help limit empiric anti-MRSA antibiotic therapy. We aimed to evaluate the use of MNS for anti-MRSA antibiotic de-escalation in hospitalized children (<18 years). Records of patients admitted between 1 January 2015 and 31 December 2020 with a presumed infectious diagnosis who were started on anti-MRSA antibiotics, had a PCR-based MNS, and a clinical culture performed were retrospectively reviewed. A total of 95 children were included with a median age (range) of 2 (0-17) years. The top three diagnosis groups were skin and soft tissue infections (n = 38, 40%), toxin-mediated syndromes (n = 17, 17.9%), and osteoarticular infections (n = 14, 14.7%). Nasal MRSA colonization and growth of MRSA in clinical cultures was found in seven patients (7.4%) each. The specificity and the negative predictive value (NPV) of the MNS to predict a clinical MRSA infection were both 95.5%. About half (n = 55, 57.9%) had anti-MRSA antibiotics discontinued in-house. A quarter (n = 14, 25.5%) were de-escalated based on the negative MNS test alone, and another third (n = 21, 38.2%) after negative MNS test and negative culture results became available. A high NPV suggests that MNS may be useful for limiting unnecessary anti-MRSA therapy and thereby a useful antimicrobial stewardship tool for hospitalized children. Prospective studies are needed to further characterize the utility of MNS for specific infectious diagnoses.